Application of mixed natural preservatives to improve the quality of vacuum skin packaged beef during refrigerated storage. (November 2020) - Yu, Hwan Hee; Kim, Yeon Jin; Park, Yeong Jin; Shin, Dong-Min; Choi, Yun-Sang; Lee, Na-Kyoung; Paik, Hyun-Dong
Abstract: This study aimed to develop an active packaging (AP) system for beef storage using vacuum skin packaging (VSP) applied with mixed natural preservatives (MNPs) consisting of grapefruit seed extract (GSE), cinnamaldehyde (CA), and nisin; and to assess its effect on the physicochemical, microbial, and antibacterial properties against food-borne pathogens in beef compared with using wrapped packaging (WP) and VSP. The pH of the AP was a medium level of WP and VSP. AP was effective in preserving beef surface color including lightness and redness. AP delayed lipid oxidation and protein deterioration of beef by 14 days and 7 days as compared to that in WP and VSP, respectively. It also slowed low microbial counts of psychrotrophic and anaerobic bacteria about 1–2 Log CFU/g and inhibited the growth of experimented food-borne pathogens compared to initial inoculated counts. Our results indicated that MNPs applied to AP could be used to extend the shelf life of beef and prevent related food poisoning.